Compact dual-band I-shaped patch antenna with longitudinal strip on inverted-T ground plane - Chawanonphithak, Yuktitath; Phongcharoenpanich, Chuwong (My University, 2014)
This paper presents a compact dual-band I-shaped patch antenna with longitudinal strip on inverted-T ground plane for wireless local area network (WLAN) applications over the frequency band of 2.400-2.484 GHz and 5.150-5.350 GHz. The I-shaped patch antenna and inverted-T ground plane are etched onto a piece of printed circuit board (PCB) with an overall size of 40 mm × 60 mm × 1.6 mm. It is excited by strip line to match impedance with a 50 ω transmission line. The measured results show that the miniaturized antenna achieves a broad operating bandwidth of 2.26-2.89 GHz and 4.92-5.83 GHz for S11<-10 dB and omnidirectional radiation pattern. The measured gains of the antenna at 2.4 GHz and 5.2 GHz frequencies are 1.90 dBi and 3.45 dBi, respectively. © 2014 IEEE.
Keywords: Compact antenna; dual-band; inverted-T ground plane; omnidirectional; wireless local area network (WLAN)